PERANAN SUMBER DAYA KONSTRUKSI DALAM KECELAKAAN KONSTRUKSI - Amal, Ali (LPPM, 2025)
One of the primary issues in construction work is construction accidents, which are largely attributed to factors related to management or construction resources. This study aims to identify the role of construction resources in the occurrence of construction accidents. It will analyze the influence of these resources based on literature reviews and observational data regarding construction accidents. The findings indicate that the technical aspects of construction resources play a significant role in the incidence of such accidents. The components of construction resources must meet performance standards, which include human resources (competent labor), financial resources (adequate funding), materials (quality materials), machinery (functional equipment), and methodologies that adhere to design specifications. It is essential for these resources to be aware of the risk levels associated with the operational tasks at hand. If any component of the construction resources fails to meet operational standards and procedures, performance or functional adjustments (calibration) must be made. The fulfillment of construction resource standards is also influenced by environmental, managerial, and organizational aspects. Management plays a critical role in controlling through supervision, monitoring, and evaluating the performance of construction resource management elements. However, this is also contingent upon the policies and capabilities of organizational leaders in managing work units and integrating construction resource components to foster a safe construction environment (Safety First and Zero Accident).